Biotransformation of flubendazole and fenbendazole and their effects in the ribwort plantain (Plantago lanceolata) - Stuchlíková, Lucie Raisová; Skálová, Lenka; Szotáková, Barbora; Syslová, Eliška; Vokřál, Ivan; Vaněk, Tomáš; Podlipná, Radka (Ecotoxicology and environmental safety, 2018)
Although veterinary anthelmintics represent an important source of environmental pollution, the fate of anthelmintics and their effects in plants has not yet been studied sufficiently. The aim of our work was to identify metabolic pathways of the two benzimidazole anthelmintics fenbendazole (FBZ) and flubendazole (FLU) in the ribwort plantain (Plantago lanceolata L.). Plants cultivated as in vitro regenerants were used for this purpose. The effects of anthelmintics and their biotransformation products on plant oxidative stress parameters were also studied. The obtained results showed that the enzymatic system of the ribwort plantain was able to uptake FLU and FBZ, translocate them in leaves and transform them into several metabolites, particularly glycosides. Overall, 12 FLU and 22 FBZ metabolites were identified in the root, leaf base and leaf top of the plant. Concerning the effects of FLU and FBZ, both anthelmintics in the ribwort plantain cells caused significant increase of proline concentration (up to twice), a well-known stress marker, and significant decrease of superoxide dismutase activity (by 50%). In addition, the activities of four other antioxidant enzymes were significantly changed after either FLU or FBZ exposition. This could indicate a certain risk of oxidative damage in plants influenced by anthelmintics, particularly when they are under other stress conditions.
Keywords: Drug uptake; Oxidative Stress; Biotransformation; oxidační stres; veterinární léky; UHPLC-MS/MS; Plantago; Fenbendazole; Drug metabolism; zvířata; Metabolic Networks and Pathways; Anthelmintics; Phytotoxicity; Flubendazole; fenbendazol; mebendazol; anthelmintika; Veterinary Drugs; Mebendazole; biotransformace; metabolické sítě a dráhy; Animals